The role of local government units in ecological solid waste management a comparative descriptive study of Bacolod and Iloilo City. - Villanueva, Elaine F. (2011.)
Ecological Solid Waste Management is one of the many environmental policies that are challenging the capacity of all governmental agencies in our country since there is a persisting problem on the current situation of our environment. The national government has devolved major responsibilities to the local government units sto assure effective public service delivery for the well-being of the people. the researchers are interested to know the actual roles that local government units in the city of Iloilo and Bacolod play in their respective areas and the existing problems that they encounter. Through interviews, content and text analysis, and archival research, the researchers are able to find the similarities and differences on the local government units' roles. Using four components of effective solid waste management, the researchers learned that Iloilo City and Bacolod City has an active Solid WasteManagement Board however there are differences in the compositionof the said Board. Moreover Iloilo City already started the Phase 1 of its Sanitary Landfill while Bacolod City is still working on closing its open dumpsite. Both cities are actually aware of their responsibilities in managing their solid waste however there are some problems, such as people's attitude and financial constraints, which hinders or slows down the effective implementation of the solid waste management in their area.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2011.
Keywords: Ecological Solid Waste Management